O enfoque constitucional da decisão de pronúncia - Bento, Patricia Stucchi (2006)
The Brazilian Constitucion of 1988 established the Democratic State of law, gave priority to the information rules of the Brazilian State, guilding those fundamental principles as a basic guildeline of its constitucional legal system, having as main event the human dignity which assumes the function of integration part to the brazilian legal system. The Human Dignity became one habilitation implement to the brazilian law system, achivieng one punishing combination with the fundamentals rights. The presumption of innocence became a constitution object, acting as accused status, revelling one kind of treatment given, to identify him as the subject of the criminal procedure, rights and garanties owner´s . The principle of in dubio pro reo prevision became understood as obligee application, due its nature of procedure instruments established as inconditional garanty of the presumption of innocence. The Criminal Procedure Law, as the constitucional rights applied, resultanted of those constitucional rights and garanties, have the preservation job of the freedom and public order. The Criminal Procedure harmony is directed to the binomial, social pacification and human freedom, reaching its action limits. The justication of punishing system beyond constitucional rights, finds its reality in the instrumentality and procedural security, that make practical the justice application, in its proportional ways. Due the constitucional prevision of the criminal procedure principles, they achieve its finality serving public order, to reach the social pacifism of the human being. With this appearance, new fundamental justifing of its existence became understood instrumentality and garantees rules to gave viabilits the justice regeneration, penalty application, right garantees and individual freedoms, saving person against state abusive acts when exercising it jus puniendi. In this security model, with a clear observation of the garantees established the in dubio pro reo application as basis for jury indictment (408 Brazilian Criminal Procedure Code) demanding full knowledge of the felony, and not doubt of its occurence and satisfactory demonstration of the felony. The criminal judge observes his atuation as due process of law seeker in jury system, by the non application of the in dubio pro societa, that is a serious violation of the human rights. The achieve the presumption of innoncence and the in dubio pro reo application reaches a constitucional status, becaming applicable rules when the criminal law do not have explicited determination about that issue, by analogy, in case of doubt to disfavour the citizen accused or offender. The reception of the article 408 (Brazilian Criminal Procedure Code) demands a new legal basis which is Brazilian Federal Constitution of 1988. A new interpretation of the article 408 (Brazilian Criminal Procedure Code) is necessary, based in the reason of the constitution principles and norms, that can not the same being explained with the same application and the same extension of other times and political system, in spite of the fact old verbal formulation